To use this method, you have to get it so that one of your variables will cancel when you add the two equations. The best way to do that with these two equations is to make the x in the first equation be -3x. You do that by multiplying it by -3.

So now you have

-3x - 6y = -6

You add that to the other equation and you get

-y = -2 or y = 2.

Then you can just plug that in to the first equation as it originally was and you get

x + 2(2) = 2

x + 4 = 2

x = -2

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now